The Effect of Total Assets Turnover, Net Profit Margin, and Return On Assets on Profit Growth in Companies Listed on the Jakarta Islamic Index 70 - Damanhur; Hajizah, Menty (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of Total Assets Turnover (TATO), Net Profit Margin (NPM), and Return on Assets (ROA) on profit growth of companies listed in the Jakarta Islamic Index 70 (JII70) during the period 2019–2023. This research employs a quantitative approach, using secondary data from companies’ annual financial statements. The sample was selected purposively, yielding 22 companies and 110 observations. Panel data regression analysis was conducted using the Fixed Effects Model (FEM), as determined by the Chow and Hausman tests. The results reveal that, in part, TATO and NPM do not significantly affect profit growth, while ROA has a positive and significant effect. Simultaneously, TATO, NPM, and ROA significantly influence profit growth. These findings indicate that asset utilization efficiency and the ability to generate profits per total asset are key drivers of profit growth among sharia companies